2018
DOI: 10.3389/fpsyg.2018.01579
|View full text |Cite
|
Sign up to set email alerts
|

Green Breaks: The Restorative Effect of the School Environment’s Green Areas on Children’s Cognitive Performance

Abstract: Restoration involves individuals’ physical, psychological, and social resources, which have diminished over the years in the process of meeting the demands of everyday life. Psychological restoration can be provided by specific environments, in particular by natural environments. Studies report a restorative effect of nature on human beings, specifically in terms of the psychological recovery from attention fatigue and restored mental resources that were previously spent in activities that require attention. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 46 publications
6
74
0
3
Order By: Relevance
“…Living close to nature is not always possible and other ways of providing opportunities for children's contact with nature should be considered. For example, schoolyards could play an important role in enhancing urban children's time spent in natural areas (Amicone et al, 2018). Introducing nature in the classroom, such as wall gardens, can also be an effective way for children to experience nature in their daily live (van den Berg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Living close to nature is not always possible and other ways of providing opportunities for children's contact with nature should be considered. For example, schoolyards could play an important role in enhancing urban children's time spent in natural areas (Amicone et al, 2018). Introducing nature in the classroom, such as wall gardens, can also be an effective way for children to experience nature in their daily live (van den Berg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…With reference to restorative environments, Herzog et al (2002) have showed the importance of a number of contextual factors in the evaluation and selection of settings for restoration; and both Scopelliti and Giuliani (2004, 2005) and Staats and Hartig (2004) have emphasized the effect of the social environment in restoration outcomes. In addition, recent studies have suggested that a relevant mechanism promoting positive outcomes can be the perception of the restorative properties of the environment during on-site experiences in urban parks (Scopelliti et al, 2016), botanical gardens (Carrus et al, 2017) and educational settings (Amicone et al, 2018). These results deserve further exploration in terms of psychological processes leading to restoration as the on-site experience goes on.…”
Section: Introductionmentioning
confidence: 99%
“…These restorative environments help reduce tiredness, allowing individuals to restore their capacities of directed attention during learning activities [4,5]. ART is the theory that has most influenced research regarding the restorative effect of nature on humans' well-being [6]. A core concept in this theory is that human beings have limited cognitive capacities, namely, limited directed attention, particularly when the point of attention is not of interest to the subject [4].…”
Section: Introductionmentioning
confidence: 99%